2019
DOI: 10.1108/vjikms-06-2019-0098
|View full text |Cite
|
Sign up to set email alerts
|

The influence of IT-competency dimensions on job satisfaction, knowledge sharing and performance across industries

Abstract: Purpose Technology makes knowledge management easier. Knowledge sharing is essential for organizational development. Job satisfaction fosters knowledge sharing. Hence, this study aims to develop an understanding of the mutual relationship between knowledge sharing and job satisfaction when both are predicted by information technology (IT)-competency dimensions such as IT-operations, IT-knowledge and IT-infrastructure in the context of company performance. Design/methodology/approach The results were achieved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 68 publications
3
39
0
1
Order By: Relevance
“…Recent papers have confirmed the relation between work skills use and job satisfaction [47]. Recent research in the information technology field have shown that organizational skills lead to job satisfaction [48].…”
Section: Professional Skill Usementioning
confidence: 90%
“…Recent papers have confirmed the relation between work skills use and job satisfaction [47]. Recent research in the information technology field have shown that organizational skills lead to job satisfaction [48].…”
Section: Professional Skill Usementioning
confidence: 90%
“…The results revealed a positive correlation between ICT use and knowledge collecting, but no association was found between ICT use and knowledge donating. However, Yeh et al [58] and Kucharska and Erickson [15] emphasized technology as a driver of knowledge sharing and further added that the digitalization of documents and the fast exploration of knowledge for its re-use are important in this regard.…”
Section: Technology Factors For Knowledge Sharingmentioning
confidence: 99%
“…Various studies have highlighted the significance of organizational level factors such as the presence of shared interaction culture [6][7][8][9], support from top management [5,10,11], and the provision of incentives/rewards [9,10,12,13]. In addition to this, the use of Information and Communication Technology (ICT) has also been focused on as an enabler and predictor of knowledge sharing for its ability to provide seamless access to knowledge for individuals to share [11,14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the increasing trend of commerce and growing competition in the 21st century, IT tools emerged quickly in today's business, for example, ESM tools. IT has not only modified the normal approach of businesses but also broken the procedure of old work environment and built changes deep in time and space (Kucharska & Erickson, 2019;Paik et al, 2017). The efficient utilization of IT tools in the organization may be a vital issue which effectively enhances the task performance (Jafar et al, 2019;Wang Chen & Benitez-Amado, 2015).…”
Section: It Competencymentioning
confidence: 99%